2013
DOI: 10.5125/jkaoms.2013.39.4.156
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical evaluation of ridge augmentation using autogenous tooth bone graft material: case series study

Abstract: ObjectivesInterest in bone graft material has increased with regard to restoration in cases of bone defect around the implant. Autogenous tooth bone graft material was developed and commercialized in 2008. In this study, we evaluated the results of vertical and horizontal ridge augmentation with autogenous tooth bone graft material.Materials and MethodsThis study targeted patients who had vertical or horizontal ridge augmentation using AutoBT from March 2009 to April 2010. We evaluated the age and gender of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 18 publications
2
37
0
1
Order By: Relevance
“…Of these, 795 were screened based on the title and/or abstract content, and 42 were selected for full‐text assessment and inclusion in the qualitative evaluation. Finally, 34 studies (Antoun, Sitbon, Martinez, & Missika, ; von Arx & Buser, ; von Arx & Kurt, ; Assenza et al., ; Bahat & Fontanessi, ; Buser, Dula, Hirt, & Schenk, ; Chiapasco, Autelitano, Rabbiosi, & Zaniboni, ; Cordaro, Amade, & Cordaro, ; Cordaro, Torsello, Morcavallo, & di Torresanto, ; Friedmann, Strietzel, Maretzki, Pitaru, & Bernimoulin, ; Her, Kang, & Fien, ; Kfir, Kfir, & Kaluski, ; Lee, Kim, Yi, & Choi, ; Lindfors, Tervonen, Sandor, & Ylikontiola, ; Lizio, Corinaldesi, & Marchetti, ; Lorenzoni, Pertl, Polansky, Jakse, & Wegscheider, ; Louis, Gutta, Said‐Al‐Naief, & Bartolucci, ; Lyford, Mills, Knapp, Scheyer, & Mellonig, ; Mattout & Mattout, ; Meloni et al., ; Merli et al., ; Miyamoto, Funaki, Yamauchi, Kodama, & Takahashi, ; Park, Brooks, Oh, & Wang, ; Parodi, Carusi, Santarelli, & Nanni, ; Proussaefs & Lozada, , ; Proussaefs, ; Sethi & Kaus, ; Torres et al., ; Uehara et al., ; Urban, Nagursky & Lozada, ; Urban, Nagursky, Lozada, & Nagy, ; Wessing, Emmerich, & Bozkurt, ; Zitzmann, Naef, & Scharer, ) were excluded from the quantitative analysis due to lack of data, and eight studies (Annibali, Bignozzi, Sammartino, La Monaca, & Cristalli, ; Buser et al., ; Chiapasco, Abati, Romeo, & Vogel, ; Fu, Oh, Benavides, Rudek, & Wang, ; Gher, Quintero, Assad, Monaco, & Richardson, ; Nowzari & Slots, ; Park et al., ; Tawil, El‐Ghoule, & Mawla, ) that reported on the primary and secondary outcomes were meta‐analyzed. The kappa value between the two reviewers was 0.92 for titles and abstract evaluation, and 0.88 for full‐text evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 795 were screened based on the title and/or abstract content, and 42 were selected for full‐text assessment and inclusion in the qualitative evaluation. Finally, 34 studies (Antoun, Sitbon, Martinez, & Missika, ; von Arx & Buser, ; von Arx & Kurt, ; Assenza et al., ; Bahat & Fontanessi, ; Buser, Dula, Hirt, & Schenk, ; Chiapasco, Autelitano, Rabbiosi, & Zaniboni, ; Cordaro, Amade, & Cordaro, ; Cordaro, Torsello, Morcavallo, & di Torresanto, ; Friedmann, Strietzel, Maretzki, Pitaru, & Bernimoulin, ; Her, Kang, & Fien, ; Kfir, Kfir, & Kaluski, ; Lee, Kim, Yi, & Choi, ; Lindfors, Tervonen, Sandor, & Ylikontiola, ; Lizio, Corinaldesi, & Marchetti, ; Lorenzoni, Pertl, Polansky, Jakse, & Wegscheider, ; Louis, Gutta, Said‐Al‐Naief, & Bartolucci, ; Lyford, Mills, Knapp, Scheyer, & Mellonig, ; Mattout & Mattout, ; Meloni et al., ; Merli et al., ; Miyamoto, Funaki, Yamauchi, Kodama, & Takahashi, ; Park, Brooks, Oh, & Wang, ; Parodi, Carusi, Santarelli, & Nanni, ; Proussaefs & Lozada, , ; Proussaefs, ; Sethi & Kaus, ; Torres et al., ; Uehara et al., ; Urban, Nagursky & Lozada, ; Urban, Nagursky, Lozada, & Nagy, ; Wessing, Emmerich, & Bozkurt, ; Zitzmann, Naef, & Scharer, ) were excluded from the quantitative analysis due to lack of data, and eight studies (Annibali, Bignozzi, Sammartino, La Monaca, & Cristalli, ; Buser et al., ; Chiapasco, Abati, Romeo, & Vogel, ; Fu, Oh, Benavides, Rudek, & Wang, ; Gher, Quintero, Assad, Monaco, & Richardson, ; Nowzari & Slots, ; Park et al., ; Tawil, El‐Ghoule, & Mawla, ) that reported on the primary and secondary outcomes were meta‐analyzed. The kappa value between the two reviewers was 0.92 for titles and abstract evaluation, and 0.88 for full‐text evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…Research on graft materials that can overcome the limitations of autogenous bone and other bony substitutes has led to the development of autogenous demineralized dentin matrix (ADDM), which is an ideal substitute for autogenous bone. The ADDM has excellent osteoinductive and osteoconductive abilities, and the recovery process induced by ADDM histologically resembles that induced by autogenous bone [5,6,7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some cases reported that autogenous tooth bone graft material made from compromised teeth was applied in bone deficient areas and achieved a good clinical efficacy [7][8][9][10][11].…”
mentioning
confidence: 99%